Vimy Ridge : a Canadian reassessment - Hayes, Geoffrey, 1961-; Bechthold, Michael, 1968-; Iarocci, Andrew, 1976- (Book collections on Project MUSE., 2007)
On the morning of April 9, 1917, troops of the Canadian Corps under General Julian Byng attacked the formidable German defences of Vimy Ridge. Since then, generations of Canadians have shared a deep emotional attachment to the battle, inspired partly by the spectacular memorial on the battlefield. Although the event is considered central in Canadian military history, most people know very little about what happened during that memorable Easter in northern France. Vimy Ridge: A Canadian Reassessment draws on the work of a new generation of scholars who explore the battle from three perspecti.